Tourist Guides in Lombok: Responsibilities, Future Career, Education, Need Assessment, and Recommendations for Future Research - Marham Jupri Hadi (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2021)
Research on tourism suggests that tourist guides are key representatives in the tourism industry as they contribute significantly to the satisfaction of visitors and affect whether or not the tourist will revisit destinations. The present article reviews the existing literature on tourist guides from diverse perspectives in the hope that it would shed light on this career brighter. It begins with the definition of tourist guides, their key roles in the tourism industry, future of tourist guides, education and training and their needs for further learning. Some recommendations for future studies are presented.